Collaboration or parallel worlds? Information literacy practices in Portuguese school libraries - Bastos, Glória (2012)
This paper presents and analyses the results of a body of master’s dissertations developed on the context of a master’s programme for teacher librarians, at Universidade Aberta, Portugal. The main focus is on the concepts and work done by teacher librarians concerning information literacy. The results are set in the context of some important and recent developments in Portuguese schools.